2008
DOI: 10.1111/j.1532-950x.2008.00464.x
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Comparison of Two Alternative Tibial Plateau Leveling Osteotomy Plates with the Original Standard in an Axially Loaded Gap Model: An In Vitro Study

Abstract: Construct stiffness in axial load varies with implant type. Implants that confer higher stiffness to the construct may result in greater fixation stability in tibial metaphyseal osteotomies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 27 publications
(58 reference statements)
1
28
1
2
Order By: Relevance
“…Risk factors beyond the ones identified in this study could predispose dogs to fibular fractures after TPLO. One study identified a large preoperative TPA, a larger tibial plateau rotation, and performing the TPLO without the use of a jig as risk factors 7 . Performing TPLO without use of a jig may have contributed to the high rate of fibular fractures identified in our study (15%), compared with previous reports (0–9.5%) 2–6 .…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Risk factors beyond the ones identified in this study could predispose dogs to fibular fractures after TPLO. One study identified a large preoperative TPA, a larger tibial plateau rotation, and performing the TPLO without the use of a jig as risk factors 7 . Performing TPLO without use of a jig may have contributed to the high rate of fibular fractures identified in our study (15%), compared with previous reports (0–9.5%) 2–6 .…”
Section: Discussionmentioning
confidence: 52%
“…Fibular fracture after TPLO has been reported but is not well characterized. A fractured fibula may be a sign of, or contributing factor to, construct failure, as suggested in a TPLO gap model, 7 where 38% of the models loaded to failure had a fibular fracture or luxation and collapse of the lateral aspect of the tibial plateau. In a report of fibular fracture after TPLO, 6 9 fibular fractures were identified.…”
mentioning
confidence: 99%
“…With interfragmentary compression, axial loads are expected to be absorbed by the bone–implant composite construct. Presumably, the results could have been different using a gap model where the plate would have buttress function, as described in other reports 30,31 …”
Section: Discussionmentioning
confidence: 85%
“…As a result of a primary loss of reduction, there has been reported a shift in position of the tibial plateau fragment, such as a mediolateral translation of the proximal fragment toward or away from the plate, a rotation in an axial plane, or tipping in a horizontal plane . Similarly, a secondary loss of reduction resulting in angular deformities or increased TPA has been reported . These findings all suggests that optimal placement of the TPLO plate, accurate rotation, and maintenance of reduction postoperatively all are critical to a successful outcome …”
mentioning
confidence: 98%